Identifikasi Bakteri Staphylococcus Aureus Pada Uang Kertas Di Pasar Jembatan Puri Kota Sorong - Evi Hudriyah Hukom; Andirwana Andirwana; Fenti A. Tupanwael; Cindy H. May (Journal of Innovative and Creativity, 2025)
Introduction: banknotes are a medium of transaction that move from one individual to another and are continuously exposed to various environmental conditions, making them potential carriers for the transmission of pathogenic microorganisms. Staphylococcus aureus is a bacterium frequently found on the surfaces of commonly touched objects and is capable of causing infections ranging from skin disorders to systemic diseases. Trading activities in markets increase the risk of bacterial contamination due to crowded interactions and moist, wet environmental conditions. Purpose: To determine the presence and identify Staphilococcus aureus on banknotes circulating in Jembatan Puri Market, Sorong City. Method: this study employed a quantitative descriptive approach with banknotes samples collected from vendors at Jembatan Puri Market in Sorong City. The surface of each banknote was swabbed and examined using the Streak Plate Method. A total of 39 banknotes samples were included in this study. Result: the examination of 39 banknote samples showed that 37 samples (94,8%) tested positive for Staphylococcus aureus, while 2 samples (5,2%) tested negative or showed no presence of Staphylococcus aureus. Conclusion: the high level of Staphylococcus aureus contamination on banknotes in Jembatan Puri Market, Sorong City, indicates that banknotes are a potential medium for bacterial transmission. These findings highlight the importance of improving hand hygienic practices among vendors and customers, as well as providing education on proper and hygienic handling of money. Additionalyy, the use of non-cash transaction methods may be considered to help reduce the risk of pathogenic bacterial contamination on banknotes.